1989
DOI: 10.1002/j.1875-9114.1989.tb04102.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity Associated with Amiodarone Therapy

Abstract: Amiodarone has been reported to cause asymptomatic increases in liver function tests in 15-55% of patients. Clinically apparent, symptomatic hepatic disease occurs less frequently, but patients have been reported to have hepatomegaly, jaundice, cirrhosis, or chronic active hepatitis. Less well recognized is the fact that amiodarone has been attributed to six deaths. We cared for a patient with amiodarone hepatotoxicity, which led us to review the literature associated with this serious condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…If this were the case, induction of CYP3A4, the main cytochrome P450 isozyme responsible for amiodarone deethylation (Fabre et al, 1993), may be a risk factor for hepatotoxicity associated with amiodarone. Although a high dosage and/or high plasma levels of amiodarone are considered to represent risk factors for hepatotoxicity associated with this drug (Pollak et al, 1990;Bravo et al, 2005), induction of CYP3A4 has so far not been reported to be a risk factor for amiodarone-associated liver injury (Rigas et al, 1986;Flaharty et al, 1989;Lewis et al, 1989). Since CYP3A4 inducers (e.g., antiepileptics such as phenytoin, phenobarbital and carbamazepine as well as rifampicin) are used quite frequently and since hepatotoxicity associated with amiodarone is potentially fatal (Lewis et al, 1989), this question is clinically important and should therefore be investigated and answered.…”
Section: Discussionmentioning
confidence: 99%
“…If this were the case, induction of CYP3A4, the main cytochrome P450 isozyme responsible for amiodarone deethylation (Fabre et al, 1993), may be a risk factor for hepatotoxicity associated with amiodarone. Although a high dosage and/or high plasma levels of amiodarone are considered to represent risk factors for hepatotoxicity associated with this drug (Pollak et al, 1990;Bravo et al, 2005), induction of CYP3A4 has so far not been reported to be a risk factor for amiodarone-associated liver injury (Rigas et al, 1986;Flaharty et al, 1989;Lewis et al, 1989). Since CYP3A4 inducers (e.g., antiepileptics such as phenytoin, phenobarbital and carbamazepine as well as rifampicin) are used quite frequently and since hepatotoxicity associated with amiodarone is potentially fatal (Lewis et al, 1989), this question is clinically important and should therefore be investigated and answered.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of amiodarone induced hypothyroidism ranges from 2-20% of patients [3,19], while the incidence of amiodarone induced hyperthyroidism is approximately 3% in areas where the diet is sufficient with iodine and 20% in those with an iodine deficient diet [3,19]. Asymptomatic increases in liver transaminases (5-15%) or hepatotoxicity (0.28%) reported as hepatomegaly, jaundice, cirrhosis or chronic hepatitis may occur [16,20]. Peripheral neuropathy can be induced by chronic administration of amiodarone with an incidence of 0.3% annually [4,21].…”
Section: Dronedarone Safety Comparison To Amiodaronementioning
confidence: 96%
“…Toxicity associated with amiodarone may be related to phospholipidosis (formation of drug-lipid complexes in lysosomes), iodine content in the chemical structure, and its long half-life [3,4,16]. Amiodarone can adversely affect the cardiovascular system as well as numerous non-cardiovascular organ systems including dermatologic, gastrointestinal, endocrine, hepatic, neurologic, ophthalmologic and pulmonary [2][3][4]16].…”
Section: Dronedarone Safety Comparison To Amiodaronementioning
confidence: 99%
“…Most individuals administered amiodarone on a chronic basis will experience at least one side effect [Vanerven & Schalij, 2010], Decrease heart rate and increase incidence of heart block, interstitial lung disease, Some individuals developed pulmonary fibrosis after a week of treatment, Amiodarone is structurally similar to thyroxin, which contributes to the effects of amiodarone on thyroid function, both under and over activity of the thyroid may occur on amiodarone treatment [Batcher, et al 1989], Corneal micro-deposits, Corneal verticillata, Abnormal liver enzyme results are common in patients on amiodarone. [Flaharty, et al 1989] According to the numerous drug interactions and adverse effects caused by amiodarone, this research investigates the effect of a novel antidysrhythmic drug, vernakalant, on reperfusion dysthymia in rats in comparison with amiodarone, standard broad spectrum antidysrhythmic drug.…”
Section: Amiodaronementioning
confidence: 99%